Serum from human burn victims impairs myogenesis and protein synthesis in primary myoblasts - Corrick, Katie L.; Stec, Michael J.; Merritt, Edward K.; Windham, Samuel T.; Thomas, Steven J.; Cross, James M.; Bamman, Marcas M. (Frontiers in Physiology, 2015)
The pathophysiological response to a severe burn injury involves a robust increase in circulating inflammatory/endocrine factors and a hypermetabolic state, both of which contribute to prolonged skeletal muscle atrophy. In order to characterize the role of circulating factors in muscle atrophy following a burn injury, human skeletal muscle satellite cells were grown in culture and differentiated to myoblasts/myotubes in media containing serum from burn patients or healthy, age and sex-matched controls. While incubation in burn serum did not affect NFκB signaling, cells incubated in burn serum displayed a transient increase in STAT3 phosphorlyation (Tyr705) after 48h of treatment with burn serum (≈+70%; P<0.01), with these levels returning to normal by 96h. Muscle cells differentiated in burn serum displayed reduced myogenic fusion signaling (phospho-STAT6 (Tyr641), ≈-75%; ADAM12, ≈-20%; both P<0.01), and reduced levels of myogenin (≈-75%; P<0.05). Concomitantly, myotubes differentiated in burn serum demonstrated impaired myogenesis (assessed by number of nuclei/myotube). Incubation in burn serum for 96h did not increase proteolytic signaling (assessed via caspase-3 and ubiquitin levels), but reduced anabolic signaling (p-p70S6k (Ser421/Thr424), -30%; p-rpS6 (Ser240/244), ≈-50%) and impaired protein synthesis (-24%) (P<0.05). This resulted in a loss of total protein content (-18%) and reduced cell size (-33%) (P<0.05). Overall, incubation of human muscle cells in serum from burn patients results in impaired myogenesis and reduced myotube size, indicating that circulating factors may play a significant role in muscle loss and impaired muscle recovery following burn injury.